Emaranhados criativos entre dança e Feldenkrais: considerações a partir de uma prática - Alex Dias Mendes Moreira (2024)
Starting from the intertwining of dance and the Feldenkrais Method, the research proposes practice as a field of investigation, stimulating creative experience and the connection between perception and action. Recognizing the Feldenkrais Method as a valuable tool for improving movement and expanding self-knowledge, the investigation sought to examine how this approach can influence and drive the emergence of creative ideas in the context of dance. The study values subjective and emotional approaches to support discoveries and discursive explanations of artistic production, recognizing in praxis the generation of creative flows. The choice of Practice as Research as a methodological path supports this process, broadening the understanding of research as an approach that considers the research subject immersed in the environment under study, emphasizing the creation of knowledge from the perspective of the researcher, who becomes the very focus of the research, along with their relationships within and with the environment. This text articulates and discusses principles, practices and modes of operation that, throughout the research process, emerged from a deep connection between memories, sensations, awareness and creative expression. This interweaving served as the starting point for a journey where bodily sensations and mental images evoked rotational movement flows, folds and twists. This flexible and adaptive approach allowed discoveries to emerge from practice and continuous observation. The constant dialog between sensation and motor response proved fundamental in exploring the intersection between dance and the Feldenkrais Method, propelling the research into a field of discovery that values subjective experience and the intimate connection between perception and action in the artistic context.